2013
DOI: 10.1172/jci66043
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing monocytes to cross-present circulating viral antigen in chronic infection

Abstract: Selection of antigens for therapeutic vaccination against chronic viral infections is complicated by pathogen genetic variations. We tested whether antigens present during persistent viral infections could provide a personalized antigenic reservoir for therapeutic T cell expansion in humans. We focused our study on the HBV surface antigen (HBsAg), which is present in microgram quantities in the serum of chronic HBV patients. We demonstrated by quantitative fluorescent microscopy that, out of 6 professional APC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 53 publications
5
73
0
Order By: Relevance
“…29,30 We demonstrated that HBsAg 1 CD14 monocytes, when differentiated to moDCs, cross-presented in vivo-captured antigen and expanded autologous HBV-specific CD4 and CD8 T cells. 17 Similarly, other studies have shown that autologous moDCs loaded with recombinant HBV antigens were capable of stimulating autologous T-cell proliferation. [37][38][39] Because of their stimulatory capacity, moDCs loaded with recombinant antigens or synthetic peptides have been administered to patients in two clinical trials.…”
Section: Potential Of Modc Vaccinesmentioning
confidence: 91%
See 3 more Smart Citations
“…29,30 We demonstrated that HBsAg 1 CD14 monocytes, when differentiated to moDCs, cross-presented in vivo-captured antigen and expanded autologous HBV-specific CD4 and CD8 T cells. 17 Similarly, other studies have shown that autologous moDCs loaded with recombinant HBV antigens were capable of stimulating autologous T-cell proliferation. [37][38][39] Because of their stimulatory capacity, moDCs loaded with recombinant antigens or synthetic peptides have been administered to patients in two clinical trials.…”
Section: Potential Of Modc Vaccinesmentioning
confidence: 91%
“…A similar observation was made in terms of mDC cytokine profiles, in which the IL-12p70 and IL-10 production was equal between HBV patients and healthy donors. 12,[14][15][16][17] Exceptions are present, however. Zhang et al 12 reported a lower frequency of mDCs in the blood of immune active pediatric patients, but not in those who were immune-tolerant.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…T cells in patients with chronic HBV infection [45]. In another study, monocyte-derived DCs retaining HBsAg recovered from chronically infected patients were able to increase the number of autologous HBV-specific T cells [46], suggesting that they are a promising adjuvant in vivo. A DNA vaccine could be another candidate: a fusion DNA encoding mouse DEC-205 linked with HBsAg successfully induced T cell and antibody responses against HBsAg in HBV transgenic mice [47].…”
Section: Immunological Intervention Against Hbv Infectionmentioning
confidence: 99%